Education and HIV/AIDS Prevention : Evidence from a Randomized Evaluation in Western Kenya - Duflo, Esther (World Bank, Washington, DC, 2012)
The authors report results from a randomized evaluation comparing three school-based HIV/AIDS interventions in Kenya: (1) training teachers in the Kenyan Government's HIV/AIDS-education curriculum; (2) encouraging students to debate the role of condoms and to write essays on how to protect themselves against HIV/AIDS; and (3) reducing the cost of education. Their primary measure of the effectiveness of these interventions is teenage childbearing, which is associated with unprotected sex. The authors also collected measures of knowledge, attitudes, and behavior regarding HIV/AIDS. After two years, girls in schools where teachers had been trained were more likely to be married in the event of a pregnancy. The program had little other impact on students' knowledge, attitudes, and behavior, or on the incidence of teen childbearing. The condom debates and essays increased practical knowledge and self-reported use of condoms without increasing self-reported sexual activity. Reducing the cost of education by paying for school uniforms reduced dropout rates, teen marriage, and childbearing.